A study of patients with acute poison: a single center experience - Chaudhari, Ashvin; Kumawat, Dalchand C. (International Journal of Research in Medical Sciences, 2018)
Background: Periodic experimental and epidemiological studies are essential to understand the pattern of poisoning in society. These studies are useful for planning of providing better and fast health care facilities to decrease poisoning connected mortality. This study was intended to assess the pattern & consequence of acute poisoning cases. Methods: This study was conducted with 100 patients admitted at a Geetanjali Medical college and hospital from June 2015 to December 2017 were studied. We retrospectively analyzed the gender, age, causes of poisoning, types of poisons, poisoning route, emergency diagnoses, outcomes, and prognoses of these patients. Results: Most of the patients were from the age group of 21 - 30 years (49 %) followed by 31-40 years (33%). Males (59%) prevailed females (41%). Out of all subjects, 53% belonged to middle socioeconomic class, whereas only 19% were from high socioeconomic class. Out of all patients, 62% were from illiterate class and 38% were literate. Suicide (77%) was the most communal nature of poisoning. Phenyl (19%) was the most commonly used poison. Mortality was found to be 4% and was mainly related to organophosphate compounds. Conclusions: Poisoning is further common in young males so they should be emotionally maintained in stressful conditions. Mortality was found significantly to organophosphate poisoning. Easy availability of this compound should be checked. Early care in tertiary care center may assistance to reduce mortality in India.